Demographic history and genetic diversity of wild African harlequin quail (Coturnix delegorguei delegorguei) populations of Kenya. Issue 24 (13th December 2021) - Ogada, Stephen; Otecko, Newton O.; Moraa Kennedy, Grace; Musina, John; Agwanda, Bernard; Obanda, Vincent; Lichoti, Jacqueline; Peng, Min‐Sheng; Ommeh, Sheila
Abstract: Hunting wild African harlequin quails ( Coturnix delegorguei delegorguei ) using traditional methods in Western Kenya has been ongoing for generations, yet their genetic diversity and evolutionary history are largely unknown. In this study, the genetic variation and demographic history of wild African harlequin quails were assessed using a 347bp mitochondrial DNA (mtDNA) control region fragment and 119, 339 single nucleotide polymorphisms (SNPs) from genotyping‐by‐sequencing (GBS) data. Genetic diversity analyses revealed that the genetic variation in wild African harlequin quails was predominantly among individuals than populations. Demographic analyses indicated a signal of rapid demographic expansion, and the estimated time since population expansion was found to be 150, 000–350, 000 years ago, corresponding to around the Pliocene–Pleistocene boundary. A gradual decline in their effective population size was also observed, which raised concerns about their conservation status. These results provide the first account of the genetic diversity of wild African harlequin quails of Siaya, thereby creating a helpful foundation in their biodiversity conservation. Abstract : This study looks into the genetic diversity and demographic history of wild African harlequin quails using mtDNA and genotyping by sequencing data. The results of this work will provide a foundation useful in its protection and biodiversity conservation.